Mobile application based on CCI standards to help children learn English as a foreign language. Issue 3 (3rd April 2021) - Sadiq, Raghad Baker; Cavus, Nadire; Ibrahim, Dogan
ABSTRACT: Many applications can be found on the Internet that are designed to help children learn English as a second language. However, it can be said that only a limited number of applications have been designed and developed by considering the important user interface design principles; these principles play an important role in mobile application design aimed at children. The main aim of this study is to develop an educational application running on a mobile phone based on the user interface design principles, particularly CCI standards together with the use of text-to-speech and voice recognition engines that will help children learn English as a foreign language. A survey was conducted in order to determine the opinions of 37 randomly selected volunteer educational technology experts and 10 randomly selected volunteer children. The opinions of a group of children showed that they were happy to use the developed application. Furthermore, it can be said that the mobile application achieved its aims in teaching English as a foreign language with the CCI standards and that the application is suitable as an educational tool. The application developed by the researchers will be beneficial for those who wish to develop Android-based educational applications for children based on CCI standards.